Prevelance of Fungal Infections to the Human Population of District Buner - Imad Ali Khan, Samiyah Tasleem, Haroon Ur Rsahid, Wali Muhammad Achakzai, Shagufta Saddozai, Tahir Azeem, Hameed Ur Rehman, Sakhi Jan, Kausar Saeed (Pakistan Journal of Medical & Health Sciences, 2023)
Aims: The current study is conducted to determine the prevalence of fungal skin infection to the human population of district Buner, Khyber Pakhtunkhwa, Pakistan. Methods: In the current study we investigate 470 patients containing the fungal skin infection in the seven tehsil of District Buner. Results: During the study there are three major infections we investigate which is present in District Buner among the fungal skin infections and it’s are the following, Tinea infection, Candidiasis infection and Pityriasis versicolor infection. . The Tinea consists of tinea capitis, tinea faciei, and tinea corporis, tinea cruris, tinea pedis and tinea Unguium. Practical Implication: The fungal skin infection is more common in this tehsil because of their humidity. We also reported the mode of the transmissions and as will is the cause of fungal skin infections in human in district Buner. We reported the proper lab procedure and the treatment of fungal skin infection in human in district Buner. Conclusion: There are three fungal infections are present one is Ringworm infection about 55% are present and Candidiasis infection and it is about 27% and the Pityriasis versicolor is 18%. We also determined the sub Tinea infection, Tinea Capitis are 35 %, Tinea Faciei is 22%, Tinea Corporis 15%, Tinea Cruris 13%, Tinea Pedis 10%, and Tinea Unguium is 05%.We determine the distributions of fungal skin infection in human with age below the ten years 25%, above the ten years is 25%, above the twenty years is 15%, above the thirty years is 17% and above the fourty years is 18%. We also investigate the ratio and tehsil wise. Tehsil Daggar consist 7%, Tehsil Gagra 8%, Tehsil Gadezai 10%, Tehsil Mandan 25%, Tehsil Chagharzi 20%, Tehsil Amazi 13% and Tehsil Khodokhel 17% is present in District Buner Khyber Pakhtunkhwa, Pakistan. Keywords: Fungal skin infection, in Human, Prevalence, Buner, Khyber Pakhtunkhwa, Pakistan.